2020
DOI: 10.1515/nleng-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Mixed convection flow in a vertical channel in the presence of wall conduction, variable thermal conductivity and viscosity

Abstract: This study theoretically investigates the effects of variable viscosity, thermal conductivity and wall conduction on a steady mixed convection flow of heat generating/absorbing fluid passes through a vertical channel. One of the channel plates moves with a constant velocity while the other is stationary. The governing flow equations are solved analytically using homotopy perturbation method (HPM). The effects of the thermophysical and hydrodynamics parameters are captured in graphs and tables. It has been obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the other hand, Jha et al 25 found that for mixed convection parameter values greater than a critical threshold, reversed flow occurs at the inner surface of the outer cylinder. Ajibade and Umar 26 investigated the effects of viscous dissipation and boundary plate thickness on a mixed convection flow with variable thermal conductivity and viscosity. On vertical parallel plates, Muhammad and Ajibade 27 investigated the effects of coupled convection and viscous dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Jha et al 25 found that for mixed convection parameter values greater than a critical threshold, reversed flow occurs at the inner surface of the outer cylinder. Ajibade and Umar 26 investigated the effects of viscous dissipation and boundary plate thickness on a mixed convection flow with variable thermal conductivity and viscosity. On vertical parallel plates, Muhammad and Ajibade 27 investigated the effects of coupled convection and viscous dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…A circular microchannel placed vertically was considered by Jha et al 24 for the examination of natural convection flow subject to temperature‐sensitive viscosity. The effect of varying thermal conductivity and viscosity on a mixed convection flow in a channel placed vertically were theoretically explored by Azibade and Umar 25 . A number of researchers, including Abu‐Nada, 26 Ajibade and Ojeagbase, 27 Wang et al, 28 and others, delved into convective flow with temperature‐sensitive viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of varying thermal conductivity and viscosity on a mixed convection flow in a channel placed vertically were theoretically explored by Azibade and Umar. 25 A number of researchers, including Abu-Nada, 26 Ajibade and Ojeagbase, 27 Wang et al, 28 and others, delved into convective flow with temperature-sensitive viscosity. The impacts of changing density, magnetic field effects, and thermal radiation on the heat transmission and fluid flow upon a tilted moving surface were examined by Abbas et al 29 According to the aforementioned review, earlier investigations on the issue at hand relied on natural convection in viscous incompressible fluid flow with linear dependency of density and viscosity on temperature.…”
mentioning
confidence: 99%
“…The deviation in viscosity and thermal conductivity on the mixed convective transportation of incompressible viscous fluid in a vertical channel was analyzed by Ajibade and Umar. 34 Manjunatha et al 35 considered a two-dimensional channel to analyze the impact of variable transportation properties under the impression of surface conditions. Again, Ajibade and Tafida 36 inspect the impact of variable transportation properties on the mixed convective coquette motion in a vertical channel.…”
Section: Introductionmentioning
confidence: 99%